In silico identification of outer membrane protein (Omp) and subunit vaccine design against pathogenic Vibrio cholerae. (December 2016) - Rauta, Pradipta Ranjan; Ashe, Sarbani; Nayak, Debasis; Nayak, Bismita
Graphical abstract: Highlights: Computational approaches were used to identify epitopes for vaccine development against Vibriocholerae . The epitopes were identified by the strategy that combine both B-cell and T-cell epitope prediction. Identified epitope (9 mer: YKSISPQDA) can be useful in designing broad spectrum peptide vaccine development. Abstract: Virulence-related outer membrane proteins (Omps) are expressed in bacteria (Gram-negative) such as V. cholerae and are vital to bacterial invasion in to eukaryotic cell and survival within macrophages that could be best candidate for development of vaccine against V. cholerae . Applying in silico approaches, the 3-D model of the Omp was developed using Swiss model server and validated byProSA and Procheck web server. The continuous stretch of amino acid sequences 26 mer: RTRSNSGLLTWGDKQTITLEYGDPAL and 31 mer: FFAGGDNNLRGYGYKSISPQDASGALTGAKY having B-cell binding sites were selected from sequence alignment after B cell epitopes prediction by BCPred and AAP prediction modules of BCPreds. Further, the selected antigenic sequences (having B-cell epitopes) were analyzed for T-cell epitopes (MHC I and MHC II alleles binding sequence) by using ProPred 1 and ProPred respectively. The epitope (9 mer: YKSISPQDA) that binds to both the MHC classes (MHC I and MHC II) and covers maximum MHC alleles were identified. The identified epitopes can be useful in designing comprehensive peptide vaccine development against V. cholerae by inducing optimal immune response.